Psychotherapy Augmentation through Preconscious Priming - Borgeat, Francois; O'Connor, Kieron; Amado, Danielle; St-Pierre-Delorme, Marie-Eve (Frontiers in Psychiatry, 2013)
Objective: To test the hypothesis that repeated preconscious (masked) priming of personalized positive cognitions could augment cognitive change and facilitate achievement of patients’ goals following a therapy. Methods: Twenty social phobic patients (13 women) completed a 36 weeks study beginning by 12 weeks of group behavioural therapy. After the therapy, they received 6 weeks of preconscious priming and 6 weeks of a control procedure in a randomized cross-over design. The Priming condition involved listening twice daily with a passive attitude to a recording of individualized formulations of appropriate cognitions and attitudes masked by music. The Control condition involved listening to an indistinguishable recording where the formulations had been replaced by random numbers. Changes in social cognitions were measured by the Social Interaction Self Statements Test (SISST). Results: Patients improved following therapy. The Priming procedure was associated with increased positive cognitions and decreased negative cognitions on the SISST while the Control procedure was not. The Priming procedure induced more cognitive change when applied immediately after the group therapy. Conclusion: An effect of priming was observed on social phobia related cognitions in the expected direction. This self administered addition to a therapy could be seen as an augmentation strategy.